2020
DOI: 10.1088/1757-899x/981/3/032070
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Geogrid Reinforced Concrete Slabs under Drop Weight Impact Loading

Abstract: Reinforced concrete (RC) structures are often subjected to extreme dynamic loading conditions, mainly caused by effects of impact loading. A countable studies have been carried out on the structural behaviour of RC slabs under static and dynamic loadings. However, it is relatively infrequent to examine the impact behaviour of RC slabs that are embedded with non-conventional reinforcement layouts. Consequently, an experimental study was performed to examine the impact behaviour of geogrid reinforced concrete sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Various methodologies and materials have been employed to enhance the durability of slabs under both static and dynamic loading conditions. Tese include shear studs [18], basalt fber-reinforced polymer (FRP) strips [19], hybrid fbers comprising hooked-end steel, polypropylene, and Kevlar [20], high-performance fber-reinforced cementitious composites (HPFRCCs) [21], prestressed concrete [22,23], ferrocement [24], internal anchorage stirrups [25][26][27], Wshaped stirrups [28], truss shear reinforcement [29][30][31], steel plates and slurry-infltrated mat concrete (SIMCON) laminates [32,33], polypropylene fber [33], geogrids [34], and carbon textiles [35]. Increasing the thickness of the slab has demonstrated efcacy in reducing damage and altering failure modes [36], while employing higher-grade concrete has shown some advantages in mitigating slab puncture [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various methodologies and materials have been employed to enhance the durability of slabs under both static and dynamic loading conditions. Tese include shear studs [18], basalt fber-reinforced polymer (FRP) strips [19], hybrid fbers comprising hooked-end steel, polypropylene, and Kevlar [20], high-performance fber-reinforced cementitious composites (HPFRCCs) [21], prestressed concrete [22,23], ferrocement [24], internal anchorage stirrups [25][26][27], Wshaped stirrups [28], truss shear reinforcement [29][30][31], steel plates and slurry-infltrated mat concrete (SIMCON) laminates [32,33], polypropylene fber [33], geogrids [34], and carbon textiles [35]. Increasing the thickness of the slab has demonstrated efcacy in reducing damage and altering failure modes [36], while employing higher-grade concrete has shown some advantages in mitigating slab puncture [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Te research approach includes a detailed comparison through computational simulations, essential for guiding design decisions in particular structural settings. Following the implementation of these reinforcement techniques [32][33][34][35][36][37], there was a noticeable transition in the primary failure mechanism from direct crushing to bending. Additionally, certain strategies have been shown to combine bending with specifc localized crushing efects, as noted in earlier investigations [25][26][27]29].…”
Section: Introductionmentioning
confidence: 99%
“…In recent developments, steel reinforcement has been replaced in concrete by the inclusion of synthetic fibers, glass, rubber, and plastics, or natural fibers such as jute, sisal, coconut, and hemp [20][21][22][23][24][25][26]. To improve the tensile strength of concrete, polymer sheets, plates, and carbon sheets have also been evaluated experimentally [27][28][29][30]. The presence of fibers in corroded beams clearly demonstrated that the fibers provided approximately 18% more strength to the corroded beams at the loading stage than the control beam before failure [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the treaded reinforcements behaved better in terms of the energy absorption and ductility properties. Geogrid-reinforced concrete (GRC) slabs were evaluated under the drop weight impact tests [27]. The results illustrated that the GRC slab specimens effectively resisted the impact force better than the RC slab specimen.…”
Section: Introductionmentioning
confidence: 99%